Analisis Dampak Citra Merek dan Promosi Terhadap Minat Membeli Sepatu Piero : (Studi Kasus di Kalangan Mahasiswa Fakultas Ekonomi Universitas Negeri Medan) - Eli Agustina Br Tarigan; Aprinawati Aprinawati (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of Brand Image and Promotion on Purchase Interest in students of the Faculty of Economics, State University of Medan. The type of research used is quantitative research with a known population. The population in this study were students of the Faculty of Economics, State University of Medan. The sampling technique in this study was by using the Probability Sampling Technique with random sampling technique. Data collection by distributing questionnaires directly to 100 respondents. The results of this study are that Brand Image has a positive and significant effect on Purchase Interest with a beta value of 0.792 and a significance of 0.000. Promotion also has a positive and significant effect with a beta value of 0.255 and a significance of 0.007. Simultaneously, both variables have a contribution of 67% to Purchase Interest R square, with 33% influenced by other factors.